Case report: Hepatic epithelioid angiomyolipoma with elevated alpha-fetoprotein and a history of breast cancer - Zhang, Xiaowei; Chen, Jun; Huang, Bifei; Wang, Lihong (Frontiers in Surgery, 2022)
Background Perivascular epithelioid cell tumors have characteristic histological and immunohistochemical profiles. Epithelioid angiomyolipomas in the liver have particularly rare characteristics. These tumors are relatively small and lack clinical and imaging specificity. Thus, they can be easily misdiagnosed as other primary or metastatic tumors prior to surgery. Due to the significant epithelioid morphology and atypia of hepatic epithelioid angiomyolipoma (HEAML), intraoperative frozen section pathologic diagnosis might be challenging. Case presentation A 33-year-old woman was admitted to our hospital for elevated alpha-fetoprotein (AFP) levels after a regular checkup following breast cancer surgery. Initially, liver cancer was suspected based on enhanced magnetic resonance imaging and color Doppler ultrasonography. Her serum AFP levels were 23.05 ng/ml. The patient underwent laparoscopic right hepatic tumor resection. Based on intraoperative cryopathology, hepatocellular carcinoma was considered a likely diagnosis. However, postoperative pathology confirmed a right HEAML. The patient underwent regular checkups for 23 months without exhibiting recurrence or distant metastasis. Conclusion HEAML can be easily misdiagnosed on preoperative imaging and intraoperative cryopathology. Medical professionals must be aware of this possibility and proceed with caution. Postoperative pathological examination with assessment of IHC markers was helpful in diagnosing HEAML. HEAML has low malignant potential. Surgical resection is the mainstay of treatment, and most patients have a good prognosis.